Big data analytics frameworks for the influence of gut microbiota on the development of tic disorder - Fan, Fei; Bian, Zhaoxiang; Zhang, Xuan; Wu, Hongwei; Wang, Simeng; Zhang, Si; Wang, Qiong; Han, Fei (Frontiers in Computational Neuroscience, 2022)
The association between gut microbiota and psychiatric disorders has received increasing research attention. Meanwhile, big data analysis has been utilized in many filed including business, human healthcare analysis, etc. The primary objective of this article was to provides insights into Big Data Analytics (BDA) to clarify the association between gut microbiota and TD (Tic disorder). Specifically, we investigated the recent studies related to gut microbiota composition differences in patients with TD compared to health people. We searched on PubMed and Embase (Ovid) databases for relevant published articles until June 15, 2021. A total of 78 TD and 62 health control stool samples were examined. Case-control design was applied in all the studies. No consensus was evident in α-diversity and β-diversity. The abundance of phyla Bacteroidetes and Firmicutes was predominant at the taxa level. Gut microbiota taxonomic differences were found between TD cases and controls, though inconsistently across studies. Further studies are needed to reveal the underlying pathophysiology of TD and correlation between TD and gut microbiota composition.